The price and employment response of firms to the introduction of minimum wages - Sebastian Link (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper studies the price and employment response of firms to the introduction of a nation-wide minimum wage in Germany. In line with previous studies, the estimated employment effect is only modestly negative and statistically insignificant. In contrast, affected firms increased prices much more frequently. The price effect is prevalent across different sectors of the economy including manufacturing and is thus not limited to low wage industries. I document that speed and degree of price pass-through were high and firms rolled over the lion's share of the costs generated by the minimum wage to their customers. Consistent with the role of price pass-through, I find considerable heterogeneity in firms' responses to the minimum wage depending on their own business expectations, product market competition, and local labor market conditions.
Keywords: J38; J08; E31; J31; 330; price pass-through; heterogeneity in minimum wage effects; firm data; Germany